Perilaku Konsumen Pembelian Produk Tabir Surya Pendekatan Theory of Planned Behavior - Sugiyanto; Chintiya Darra Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia has become one of the countries with significantly high sales in the beauty product industry, particularly sunscreen products. Various brands strive to attract consumer attention by offering different innovations and benefits. Consequently, companies need to find ways to increase awareness and consumer loyalty towards sunscreen products by understanding factors such as attitude, subjective norms, and perceived behavioral control. This research was conducted with the main objective of understanding consumer purchasing behavior of sunscreen products through the TPB approach. Additionally, this study was conducted to provide theoretical benefits by enhancing insights and knowledge related to consumer behavior, especially in terms of consumer decision-making and consumer loyalty based on the TPB approach. The sampling method used was non-probability sampling, specifically purposive sampling. Data analysis was conducted using the Structural Equation Modeling (PLS-SEM) method with a sample size of 199 respondents. The results of this study prove that attitude, subjective norm, and perceived behavioral control have a positive impact on consumer decisions directly or indirectly through consumer loyalty. Moreover, consumer decision-making positively influences consumer loyalty. This research contributes to companies in designing marketing strategies to shape consumer decision-making and consumer loyalty towards sunscreen products. Keywords: Theory of Planned Behavior, Attitude, Subjective Norm, Perceived Behavioral Control, Consumer Decisions, Consumer Loyalty.